PENGARUH KOMITMEN DAN MOTIVASI TERHADAP KINERJA KADER POS PELAYANAN TERPADU (POSYANDU) - Bidayati, Utik (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2017)
This study aimed to analyze the eï¬ ect of commitment and motivation on the performance of health cadres in the village Sidomoyo, Godean, Sleman. The sample is determined by purposive sampling method. Data collected by providing a list of questions to respondents on aï¬ ective commitment, commitment to sustainability, normative commitment, motivation and performance of health cadres. The results obtained indicate that all the variables committed no signiï¬ cant eï¬ ect on performance. Only the motivation variable that has signiï¬ cant impact on the performance of cadres Yandu.